Rules on Wage Standard to Improve Workers’ Living Needs in the Perspective of Maqasid Al-Shari’ah - Arifuddin Muda Harahap (AHKAM : Jurnal Ilmu Syariah, 2018)
The components of living needs that become the reference in determining the minimum wage in Indonesia have changed four times. These changes have occurred to adjust the development of what are regarded as necessities. There are necessities that at first considered less critical, but then become important. In Islam, there are five essential elements of human needs, known as maqasid al-shari’a. These necessities are divided into three categories: daruriyya, hajiyya, and tahsiniyya. This article examines how the component of living necessities according to the concept of maqasid al shari’a is applied in the minimum wage regulation. This article argues that the determination of minimum wage standard has considered the current standard of living. Most of the components of Kebutuhan Hidup Layak or Decent Living Needs (DLN) include in the area of daruriyya and hajjiya, and only a few are in the area of tahsiniyya. The addition and improvement of the components of needs become evidence for the consideration of the level of needs, from daruriyya to hajiyya, and then tahsiniyya. This changes show the change of law in line with current development.